2009
DOI: 10.1016/j.ijrobp.2008.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Tumor Volume Predicts for Recurrence and Death in Head-and-Neck Cancer

Abstract: Purpose To evaluate the prognostic value of metabolic tumor volume measured on 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging and other clinical factors in patients treated for locally advanced head and neck cancer at a single institution. Materials/Methods From March 2003 to August 2007, 85 patients received PET/CT-guided chemoradiotherapy for HNC. Metabolically active tumor regions were delineated on pretreatment PET scans semi-automatically using custom software. We evaluated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 24 publications
9
138
2
Order By: Relevance
“…Allal et al [7] and Roh et al [8] found that high FDG uptake correlated with advanced pT and pN stages. However, in several studies, the SUV max of primary tumor or all lesions, including regional metastatic lymph nodes, was not confirmed as a significant factor predicting clinical outcome in the patients with HNSCC undergoing radiation therapy with or without chemotherapy [11][12][13][26][27][28]. In our results, the lower The pT stage is defined as the extent of primary tumor in terms of size and invasion into the adjacent structure.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Allal et al [7] and Roh et al [8] found that high FDG uptake correlated with advanced pT and pN stages. However, in several studies, the SUV max of primary tumor or all lesions, including regional metastatic lymph nodes, was not confirmed as a significant factor predicting clinical outcome in the patients with HNSCC undergoing radiation therapy with or without chemotherapy [11][12][13][26][27][28]. In our results, the lower The pT stage is defined as the extent of primary tumor in terms of size and invasion into the adjacent structure.…”
Section: Discussioncontrasting
confidence: 77%
“…MTV is obtained by FDG PET/CT using dedicated software which measures the volume of FDG accumulation based on the high tumor-to-background intensity ratio after attenuation correction [12]. Because of the good correlation between the MTV and the GTV assessed by other imaging tools such as CT [11,12], we can expected that MTV may be another important factor to be considered in the management of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two studies performed a validation on an independent dataset (Hofheinz et al, 2015;Tang et al, 2012). The first study (La et al, 2009) included 85 patients and showed that an increase of MTV of 17 cm 3 (from the 25th to 75th percentile) was significantly correlated with an increased risk of death (HR 2.1). The authors validated their results on a dataset of 83 patients treated in the same institution after the original dataset (Tang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%